2012
DOI: 10.1002/hed.23156
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of vascular endothelial growth factor in patients with head and neck cancer: A meta‐analysis

Abstract: Our meta-analysis supports that VEGF overexpression is an available poor predictor for patients with head and neck cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 50 publications
0
22
0
3
Order By: Relevance
“…Thus, overexpression of VEGF was found in head and neck cancer [23,24]. By inducing proliferation of lymphatic endothelia cell and development of lymphatic vessels, VEGF-C and VEGF-D contributed to lymphatic metastasis of papillary thyroid carcinoma [25].…”
Section: Non-digestive Cancersmentioning
confidence: 99%
“…Thus, overexpression of VEGF was found in head and neck cancer [23,24]. By inducing proliferation of lymphatic endothelia cell and development of lymphatic vessels, VEGF-C and VEGF-D contributed to lymphatic metastasis of papillary thyroid carcinoma [25].…”
Section: Non-digestive Cancersmentioning
confidence: 99%
“…For instance, a recent meta-analysis on 6.781 patients confirmed the negative impact of epidermal growth factor receptor (EGFR) overexpression, especially in laryngeal squamous cell carcinoma [30]. Similar negative prognostic impact was shown for vascular endothelial growth factor (VEGF) overexpression [31]. These are just some examples of the most recent discoveries for H&N cancer patients.…”
Section: Discussionmentioning
confidence: 78%
“…Curiously, these findings are, on the whole, at odds with those drawn from two previous meta‐analyses examining VEGF expression in head and neck cancers . A recent 2013 meta‐analysis of 47 original studies reporting a total of 3476 tumor samples concluded that VEGF overexpression predicts poorer survival and greater risk of lymph node metastasis, whereas an earlier 2005 meta‐analysis demonstrated an association with poorer 2‐year survival, although not with risk of nodal metastasis .…”
Section: Discussionmentioning
confidence: 91%